Implementing a Clinical Nurse Leader Shared Governance to Raise Nursing-Reported Empowerment - Rankin, Veronica (My University, 2018)
The Clinical Nurse Leader role is the newest master’s level role added to the profession of nursing. Literature supports the use of shared governance to promote nursing empowerment which inturn enhances nurse engagement, autonomy, satisfaction, and retention. Based on Kanter’s Structural Empowerment Theory, this Doctor of Nursing Practice project used a descriptive survey design to assess the effect of nurse-reported empowerment before and two months after implementation of a Clinical Nurse Leader shared governance council at a medical center using the Conditions for Workplace Effectiveness Questionnaire-II. In order to help steer the progress of the council and ensure standardization within the system’s current shared governance policy, an advisory council was also instituted. Data analysis of the pre and post intervention results reveal a positive increase in empowerment scores within five of the six domain subscales of the questionnaire. The project outcomes support the positive impact of shared governance on nurse-reported empowerment. Replication of this project can help assess current work environments in order to identify needed changes to promote nurse engagement, autonomy, work satisfaction and retention.
This project centers on the Clinical Nurse Leader role and shared governance's impact on nursing empowerment.
Keywords: clinical nurse leader, empowerment, shared governance